Effect of microwave pretreatment on the properties of particleboard made from para rubber wood sawdust with the addition of polyhydroxyalkanoates - Jutarut Lewkittayakorn,; Piyaporn Khunthongkaew,; Wilaiwan Chotigeat,; Kumar Sudesh, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The aim of this study was to investigate the effect of microwave pretreatment on the properties of particleboard made from para rubber wood sawdust with the addition of polyhydroxyalkanoates (PHAs). Para wood sawdust was pretreated with microwaves at different wattages (400, 600 and 800 W) and pretreatment times (5, 10 and 15 min) before being mixed with 10 wt. % of pure PHAs and 10 wt. % freeze-dried cells which contained 46.90% wt. % PHA, in order to make particleboard. The physical and mechanical properties of the particleboard panels obtained were also tested based on the Japanese Industrial Standards A 5098 for particleboard (JIS A5908) including modulus of rupture (MOR), internal bonding (IB), water absorption (WA) and thickness swelling (TS). The results showed that only panel made from 10 wt. % freeze-dried cells and treated with 400 watts for 5 min passed the minimum requirement of IB (1.62 ± 0.06 MPa) and nearly passed that of MOR (7.86 ± 0.67 MPa) but not passed that of WA (40.09 ± 6.53%) and TS (34.69 ± 5.43%). The panels without the addition of PHA cannot test WA and TS values because the panels dispersed immediately when submerged in water. The MOR of panels decreased with increasing wattages and pretreatment time. The wattage and pretreatment time of microwave had little effect on the WA and TS. Based on this study, microwave treatment is an appropriate method for the pretreatment of materials and PHAs can be promoted as potential additives for making particleboard.